Work in Progress: Enhancing Sewage Systems Monitoring Through the Integration of Optical Fibre Sensors in IoT - Bustamante, Heriberto (2024)
Efficient monitoring of sewage systems networks and their pump stations is vital to avoid environmental spills and enhance customer safety. This paper proposes the integration of optical fibre sensors (OFSs) into an Internet of Things (IoT) platform for better monitoring of such sewage networks. The work addresses key challenges such as scalability and interoperability of an IoT platform that supports seamless OFS-to-Cloud connectivity. The proposed platform leveragescompression algorithms and edge devices to optimize data communication. This platform is based on 28 different OFSs that have been set up in a laboratory environment to simulate a similar set up in a sewage network. This work achieved 50% compression ratio for the data collected from the OFSs andAmazon Web Services (AWS) S3 cloud system is used for data storage. This work is conducted in collaboration with Sydney Water.